Assessment of Quality of Life of Free Anterolateral Thigh Flap for Reconstruction of Tissue Defects of Total or Near-Total Glossectomy. (10th October 2020) - Zhang, Sanke; Wu, Shuang; Liu, Lei; Zhu, Dandan; Zhu, Qiuyu; Li, Wenlu
Abstract : Background . The aim of this study was to evaluate quality of life of free anterolateral thigh flap (ALTFF) for reconstruction of tissue defects of total or near-total glossectomy. Methods . Quality of life was assessed by means of the University of Washington Quality of Life (UW-QOL) and the 14-item Oral Health Impact Profile (OHIP-14), after 12 months postoperatively. Results . 65 of 79 questionnaires were returned (82.27%). In the UW-QOL, the best-scoring domain was "shoulder, " whereas the lowest scores were for "chewing" and "pain." In the OHIP-14, the lowest-scoring domain was "handicap, " followed by "Social disability" and "Psychological disability." Conclusion . Free anterolateral thigh perforator flaps for reconstruction of total or near-total glossectomy defects after cancer resection would have significantly influenced the patients' oral functions and quality of life.